2018
DOI: 10.1001/journalofethics.2018.20.5.sect1-1805
|View full text |Cite
|
Sign up to set email alerts
|

Does Family Presence in the Trauma Bay Help or Hinder Care?

Abstract: Family presence during a pediatric resuscitation remains somewhat controversial. Opponents express concern that family presence would be detrimental to team performance and that exposure to such a traumatic event could put family members at risk of posttraumatic stress. Proponents argue that family presence affords families a sense of closure by easing their anxieties and assuring them that everything was done for their loved ones in addition to improving clinicians' professional behavior by humanizing the pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Reviewing the possible geographic or situational placements of family members in the ED setting was a priority area of exploration for the MDT panel, as ED-based medical experts highlighted literature that supported family/caregiver presence at the bedside improved emotional and psychological outcomes for surviving family members when they are observers of the resuscitation of their family member. 12 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reviewing the possible geographic or situational placements of family members in the ED setting was a priority area of exploration for the MDT panel, as ED-based medical experts highlighted literature that supported family/caregiver presence at the bedside improved emotional and psychological outcomes for surviving family members when they are observers of the resuscitation of their family member. 12 …”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the panel identified and debunked perceptions by participating MDT members that families would feel unduly emotionally burdened by involvement in the resuscitative process; rather, medical literature suggests otherwise. 12 Investigating agencies had incorrectly perceived that observing the resuscitation or death of an infant would result in negative emotional outcomes and increased trauma for the caregiver/family member. Finally, also explored was confusion around consent for various medical and postmortem interventions (like radiologic imaging or lab testing) and organ donation, with strong recommendation for continued collaborative decision-making across sectors in partnership with involved family members.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies recommend family presence during resuscitation (Davidson et al., 2017; Joyner, 2018; Vincent & Lederman, 2017). It is already known that there is a clear need for a member of the healthcare team to provide support when parents are present during pediatric resuscitation (McAlvin & Carew‐Lyons, 2014; Mentzelopoulos et al., 2021; Pemberton & Howarth, 2023; Topjian et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Family-witnessed resuscitation refers to the presence of a family member being in the room, or in an area that allows the family to see or get physical contact with the patient, during a lifesaving procedure (Joyner Jr., 2018). Studies have shown that family members and patients support this practice.…”
Section: Introductionmentioning
confidence: 99%